Cloning, Expression, and Purification of Nucleoside Diphosphate Kinase from Acinetobacter baumannii. (11th April 2013) - Sikarwar, Juhi; Kaushik, Sanket; Sinha, Mau; Kaur, Punit; Sharma, Sujata; Singh, Tej P.
Abstract : Acinetobacter baumannii is a multidrug resistant pathogenic bacteria associated with hospital acquired infections. This bacterium possesses a variety of resistance mechanisms which makes it more difficult to control the bacterium with conventional drugs, and, so far no effective drug treatment is available against it. Nucleoside diphosphate kinase is an important enzyme, which maintains the total nucleotide triphosphate pool inside the cell by the transfer of γ -phosphate from NTPs to NDPs. The role of nucleoside diphosphate kinase (Ndk) has also been observed in pathogenesis in other organisms. However, intensive studies are needed to decipher its other putative roles in Acinetobacter baumannii . In the present study, we have successfully cloned the gene encoding Ndk and achieved overexpression in bacterial host BL-21 (DE3). The overexpressed protein is further purified by nickel-nitrilotriacetic acid (Ni-NTA) chromatography.